ARSENIC CONTENT AND PHENOLIC COMPOUNDS IN PARSLEY (PETROSELINUM CRISPUM (MILL.) FUSS) AND CELERY (APIUM GRAVEOLENS L.) CULTIVATED IN VOJVODINA REGION, SERBIA - Pajević, Slobodanka; Mimica-Dukić, Neda; Nemeš, Ivana; Župunski, Milan; Simin, Nataša; Watson, Malcolm; Arsenov, Danijela (Food and Feed Research, 2021)
Randomly collected samples of parsley and celery from different localities were analyzed to determine their quality based on arsenic concentrations, phenolic constituents and the antioxidant capacity of their edible parts. Arsenic concentrations were found in the range: parsley root (0.16 μg/g d.m.) < celery root (0.19 μg/g d.m.) < parsley leaf (0.35 μg/g d.m.) < celery leaf (0.45 μg/g d.m.). Total phenolic contents in roots were similar in both species and varied significantly depending on the cultivation site: 5.03-9.18 mg eqGA/g DE in parsley and 5.04-8.50 mg eqGA/g DE in celery. Lower total flavonoids content was recorded in celery. Among the phenolic acids, ferulic, chlorogenic and several cinnamic acids dominated. Apigenin and its glucosides dominated among flavonoids. Based on the principal component analysis (PCA) it can be concluded that the As content varied depending on the geographical origin of the samples. Also, phenolic compounds showed a significant contribution on PCA clustering, indicating that the cultivation site has a clear significant impact on the metabolites profile, while As content in plants did not significantly affect phenolic compound profile.
Keywords: arsenic; vegetables; antioxidative response; phenolic compounds; PCA analysis